From richer to poorer: successful invasion by freshwater fishes depends on species richness of donor and recipient basins. (3rd May 2016) - Fitzgerald, Daniel B.; Tobler, Michael; Winemiller, Kirk O.
Abstract: Evidence for the theory of biotic resistance is equivocal, with experiments often finding a negative relationship between invasion success and native species richness, and large‐scale comparative studies finding a positive relationship. Biotic resistance derives from local species interactions, yet global and regional studies often analyze data at coarse spatial grains. In addition, differences in competitive environments across regions may confound tests of biotic resistance based solely on native species richness of the invaded community. Using global and regional data sets for fishes in river and stream reaches, we ask two questions: (1) does a negative relationship exist between native and non‐native species richness and (2) do non‐native species originate from higher diversity systems. A negative relationship between native and non‐native species richness in local assemblages was found at the global scale, while regional patterns revealed the opposite trend. At both spatial scales, however, nearly all non‐native species originated from river basins with higher native species richness than the basin of the invaded community. Together, these findings imply that coevolved ecological interactions in species‐rich systems inhibit establishment of generalist non‐native species from less diverse communities. Consideration of both the ecological and evolutionary aspects of community assembly is critical to understanding invasion patterns. Distinct evolutionary histories in different regions strongly influence invasion of intact communities that are relatively unimpacted by human actions, and may explain the conflicting relationship between native and non‐native species richness found at different spatial scales.